VID 2021
DOI: 10.1553/0x003ccff2
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Profile, Previous Employment and Economic Integration of Refugees: An Austrian Case Study

Abstract: In 2015, large numbers of forced migrants crossed the borders to the European Union and the influx of new arrivals has led to the important question of implications for the host societies. This article assesses the labour market profile and previous employment of the recent inflows of displaced persons, mainly coming from Syria, Iraq and Afghanistan. Moreover, sectoral unemployment rates and trends in job openings in different economic branches in the host society are compared to the profiles of the refugee po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Bakker et al (2017) talk about a 'refugee entry effect', stressing, in particular, the initial disadvantage that refugees usually 1. face at the beginning of their working career in the host country that tends to decrease (but rarely disappear) over time. Both personal characteristics of refugees and host country-specific characteristics are responsible for refugees' penalization (Bevelander, 2016;Rengs et al, 2017).…”
Section: Introduction the Refugee Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…Bakker et al (2017) talk about a 'refugee entry effect', stressing, in particular, the initial disadvantage that refugees usually 1. face at the beginning of their working career in the host country that tends to decrease (but rarely disappear) over time. Both personal characteristics of refugees and host country-specific characteristics are responsible for refugees' penalization (Bevelander, 2016;Rengs et al, 2017).…”
Section: Introduction the Refugee Gapmentioning
confidence: 99%
“…Second, other characteristics, in many cases unobserved, such as the reason for migration, help to explain differences between different categories of immigrants. Refugees may lack personal motivation compared with other migrants, especially the economic ones (Campbell, 2014;Rengs et al, 2017). Third, in his labelling theory, Zetter (1991Zetter ( , 2007 ascribes to the mechanism of identity redefinition a role of its own in remoulding refugees as passive victims in need of assistance, perpetuating their dependency and disadvantage.…”
Section: Introduction the Refugee Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a lack of formal proof and unavailability of professional certification, refugees cannot obtain the desired and full advantages of working in the host country [23]. So, such refugees are more inclined toward entrepreneurship to tackle the threat of unemployment and low-wage jobs [24]. The author of [25] shows that 10% of the refugees in their study started their businesses after staying five years in Australia.…”
Section: Concept Of Entrepreneurial Refugeesmentioning
confidence: 99%
“…In addition, some studies suggested that people across age, education and income background were more likely to accept refugees from a similar ethnicity (Martén et al, 2019) probably because they feel a sense of shared identity and commonality (Halabi & Nadler, 2017). Furthermore, existing studies address that people who work in farming and agriculture are generally more accepting of refugees than those in other occupations (Rengs et al, 2017). One possible explanation was that refugees are often willing to work for lower wages than locals, which can help farmers to reduce labor costs (İçduygu & Diker, 2017).…”
Section: Factors Influencing Attitudes Of Refugee-hosting Populationsmentioning
confidence: 99%